The American Girl Goes to War: Women and National Identity in U.S. Silent Film - Clarke, Liz (Rutgers University Press, 2022)
During the 1910s, films about war often featured a female protagonist. The films portrayed women as spies, cross-dressing soldiers, and athletic defenders of their homes—roles typically reserved for men and that contradicted gendered-expectations of home-front women waiting for their husbands, sons, and brothers to return from battle. The representation of American martial spirit—particularly in the form of heroines—has a rich history in film in the years just prior to the American entry into World War I. The American Girl Goes to War demonstrates the predominance of heroic female characters in in early narrative films about war from 1908 to 1919. American Girls were filled with the military spirit of their forefathers and became one of the major ways that American women’s changing political involvement, independence, and active natures were contained by and subsumed into pre-existing American ideologies.
https://katalog.adlr.link/Record/51-9781978810150